Oleic Acid Coated Gelatin Nanoparticles Impregnated Gel for Sustained Delivery of Zaltoprofen: Formulation and Textural Characterization - Vishal Pande (Advanced Pharmaceutical Bulletin, 2015)
Purpose: In the present study, we have formulated zaltoprofen loaded, surface decorated, biodegradable gelatin nanogel and evaluated its texture characterization.